Preparation method of metal organic framework based on ionic liquid, product and application in carbon dioxide cycloaddition reaction

By preparing biimidazole-type ionic liquid under acidic conditions and forming chemical bonds with metal bromide, a metal organic framework based on ionic liquid with high catalytic activity was prepared, which solved the problems of catalyst recovery difficulties and side reactions in the prior art, and achieved efficient CO2 cycloaddition reaction under normal pressure and mild conditions.

CN119751907APending Publication Date: 2025-04-04ZHEJIANG MEDICAL COLLEGE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411926138.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The prior art has problems such as difficulty in recovering catalysts, occurrence of side reactions, and low selectivity in CO2 cycloaddition reactions, especially in the application of them under mild conditions and under low CO2 pressures.

Method used

A preparation method of a metal organic frame based on ionic liquid is adopted to prepare a bisimidazole-type ionic liquid by conducting a quaternary amination reaction under acidic conditions, and mixing it with metal bromide for a short time at room temperature to form chemical bonds to prepare a metal organic frame based on ionic liquid with high catalytic activity.

Benefits of technology

It realizes efficient catalytic CO2 cycloaddition reaction under normal pressure and mild conditions, has high catalytic activity, and has mild process conditions and short time, which simplifies the process flow.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751907A_ABST
    Figure CN119751907A_ABST
Patent Text Reader

Abstract

The present invention discloses a preparation method, product and application of a metal organic framework based on ionic liquid in carbon dioxide cycloaddition reaction, wherein the preparation method comprises: (S1) using short-chain imidazole and short-chain aldehyde as raw materials, carrying out quaternization reaction under acidic conditions to prepare a biimidazole ionic liquid; (S2) mixing the biimidazole ionic liquid prepared in step (S1), metal bromide and solvent, and mixing at room temperature for a period of time to obtain a metal organic framework based on ionic liquid. The preparation method disclosed by the present invention has mild process conditions and short time, and the prepared product is used to catalyze CO2 cycloaddition reaction, has high catalytic activity, and can achieve high conversion of substrate under normal pressure (CO2 pressure is 0.1MPa) and mild conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of carbon dioxide cycloaddition reaction, and in particular to a preparation method of a metal organic framework based on ionic liquid, a product and an application of the metal organic framework in carbon dioxide cycloaddition reaction. Background Art

[0002] Over the past few decades, due to the excessive use of fossil fuels, the concentration of carbon dioxide (CO2) in the atmosphere has increased by about 30%, resulting in a significant increase in surface temperature. Limiting global warming through the storage and utilization of CO2 is an important strategy. Among them, converting CO2 into high-value-added chemicals, cyclic carbonates, through cycloaddition reactions is an attractive solution. This is because cycloaddition reactions have excellent atom economy, and cyclic carbonates have a wide range of applications as secondary battery electrolytes, intermediates and solvents in the chemical industry. However, due to the thermodynamic stability and kinetic inertness of CO2, catalysts are usually required to accelerate the cycloaddition reaction. In this context, various catalysts, including ionic liquids (ILs) and metal-organic frameworks (MOFs), have been used in the cycloaddition reaction of epoxides with CO2.

[0003] There is no doubt that ILs are efficient catalysts for converting CO2 into cyclic carbonates, but due to their miscibility with epoxides and cyclic carbonates, ILs are difficult to separate from the reaction medium. In comparison, MOFs are insoluble in cycloaddition reaction systems, but due to their low activity, they usually require the assistance of co-catalysts such as tetrabutylammonium bromide (TBAB) and hexadecyltrimethylammonium bromide (CTAB). However, this may trigger the occurrence of side reactions, thereby reducing the selectivity of the system. In addition, co-catalysts are often small molecular compounds and may be difficult to efficiently recover after the reaction. At the same time, the addition of co-catalysts may also bring potential environmental unfriendly problems or increase the burden of waste treatment.

[0004] Based on the above results, combining ILs with MOFs may be an effective strategy to improve the efficiency of CO2 conversion. For example, Hu et al. (Hu YL, Zhang RL, Fang D. Quaternary phosphonium cationic ionic liquid / porous metal–organic framework as an efficient catalytic system for cycloaddition of carbon dioxide into cyclic carbonates [J]. Environmental Chemistry Letters, 2019, 17: 501-508.) used IL (dodecyl tributyl phosphonium bromide, [P 12,4,4,4 ]Br) as a catalyst, combined with MOF (MIL-53(Cr), MIL stands for Lavoisier Institute material) as a co-catalyst, a dual catalytic system was constructed to achieve the cycloaddition reaction of CO2 and epoxides. Under 1.0MPa CO2 and 100℃, a cyclic carbonate yield of more than 96% was obtained, which was attributed to the chromium active sites of MIL-53(Cr) and IL[P 12,4,4,4]Br synergistic effect. This exciting discovery shows that it is feasible to combine MOFs with ILs for CO2 conversion, but simply physically mixing ILs with MOFs still has the problem of difficulty in recovering ILs. Grafting ILs onto MOFs through chemical bonds has been shown to be an effective method to simplify the recovery of ILs. Feng et al. (Feng N, Tao Y, Chen C, et al. Bottom-up fabrication of DABCO-based bicationic ionic liquid-grafted MIL-101(Cr): Facilitating simultaneous activation of CO2 and epoxides for cyclic carbonate synthesis[J]. Separation and Purification Technology, 2025, 354: 128851.) synthesized a triethylenediamine-based dicationic IL grafted MIL-101(Cr) (called Cl[TNH2]Cl@MIL-101(Cr)) by a post-modification method, that is, MIL-101(Cr) was first prepared, and then triethylenediamine and ethyl chloride were grafted onto the ligand of MIL-101(Cr) through covalent bonds to generate Cl[TNH2]Cl@MIL-101(Cr). This IL-modified MOF exhibits high catalytic activity for CO2 conversion, achieving a yield of up to 97.8% of chloropropylene carbonate at 104.5°C and 1.07MPa CO2 without the addition of any co-catalyst. Lin et al. (Lin J, Luo J, Zhang M, et al. Incorporation of a carboxyl-functionalized imidazolium-based ionic liquid into a UiO-66 type MOF for chemical fixation of CO2 into carbonates [J]. Catalysis Science & Technology, 2024, 14 (16): 4496-4505.) prepared an IL-modified UiO-66 type MOF using a mixed ligand composed of terephthalic acid and IL (1,3-dicarboxymethyl imidazolium bromide). The MOF showed excellent catalytic activity under optimized conditions (2.2MPa CO2, 110°C), with a conversion rate of propylene oxide as high as 98.2%.

[0005] The above studies have shown that IL-modified MOFs are effective catalysts for CO2 cycloaddition reactions. However, they are usually prepared by high-temperature, high-pressure hydrothermal methods. In addition, cycloaddition reactions usually require high CO2 pressures. Therefore, it remains a major challenge to explore the synthesis of ILs-based MOFsc materials under mild conditions and apply them as efficient catalysts in cycloaddition reactions under low CO2 pressures. Summary of the invention

[0006] In response to the problems existing in the prior art, the present invention discloses a method for preparing a metal organic framework based on ionic liquid. The preparation process conditions are mild and the time is short. The prepared product is used to catalyze CO2 cycloaddition reaction. It has high catalytic activity and can achieve high conversion of the substrate under normal pressure (CO2 pressure is 0.1 MPa) and mild conditions.

[0007] The specific technical solutions are as follows:

[0008] A method for preparing a metal organic framework based on ionic liquid comprises the following steps:

[0009] (S1) using short-chain imidazole and short-chain aldehyde as raw materials, and carrying out a quaternization reaction under acidic conditions to prepare a bisimidazole-type ionic liquid;

[0010] (S2) mixing the bisimidazolium ionic liquid prepared in step (S1), the metal bromide and the solvent, and mixing them at room temperature for a period of time to obtain the ionic liquid-based metal organic framework.

[0011] The present invention develops a method for simply preparing biimidazole ionic liquid-based MOFs, which only requires short-term mixing at room temperature without the need for high-temperature and high-pressure hydrothermal reactions to achieve chemical bonding between ionic liquids and metals, thereby preparing metal-organic framework materials based on ionic liquids.

[0012] In step (S1):

[0013] Preferably, the short-chain imidazole is selected from one or more of 1-(3-aminopropyl)imidazole, 1-(2-hydroxyethyl)imidazole, and 4,5-dimethylimidazole; more preferably, 1-(3-aminopropyl)imidazole.

[0014] Preferably, the short-chain aldehydes are selected from one or more of formaldehyde, glyoxal, butyraldehyde and glutaraldehyde; more preferably, they are a mixture of formaldehyde and glyoxal.

[0015] Preferably, the short-chain aldehydes are added in the form of an aqueous solution, such as formaldehyde is added in the form of a formaldehyde aqueous solution, and glyoxal is added in the form of a glyoxal aqueous solution.

[0016] Preferably, the molar ratio of short-chain imidazole to short-chain aldehyde is (1-2):1;

[0017] More preferably, the molar ratio of the short-chain imidazole to the short-chain aldehyde is (1.0-1.2):1.

[0018] In step (S1):

[0019] Preferably, the pH value of the acidic condition is 4.0 to 5.0;

[0020] In the present invention, the raw material system is adjusted to a suitable pH value by adding an acidic substance; the acidic substance is selected from common types in the art, such as acetic acid.

[0021] Preferably, the quaternization reaction is carried out at room temperature.

[0022] After the reaction, the prepared product solution is adjusted to neutrality by adding alkali, and then subjected to post-treatment such as washing and drying to obtain an intermediate product.

[0023] In step (S2):

[0024] Preferably, the metal bromide is selected from indium bromide and / or zinc bromide;

[0025] Preferably, the solvent is selected from ethanol.

[0026] In step (S2):

[0027] Preferably, the molar ratio of the bisimidazolium ionic liquid to the metal bromide is 1:(0.3-3.0); more preferably, they are added in an equimolar ratio, at which point the reaction yield is higher.

[0028] Preferably, the concentration of the metal bromide in the solvent is 0.05 to 0.5 mol / L.

[0029] To ensure sufficient reaction of the raw materials, preferably, the bisimidazolium ionic liquid and the metal bromide are mixed with a solvent respectively, and then the reaction is carried out after preparing solution A and solution B respectively.

[0030] Preferably, the stirring and mixing at room temperature is not less than 10 min; more preferably, 10 to 20 min.

[0031] After simple mixing in step (S2), chemical bonding is formed between the bisimidazolium-type ionic liquid and the metal bromide.

[0032] The invention also discloses a metal organic framework based on ionic liquid prepared according to the method.

[0033] The invention also discloses a carbon dioxide cycloaddition reaction, which uses carbon dioxide and epoxide as raw materials and the above-mentioned metal organic framework based on ionic liquid as a catalyst.

[0034] Preferably, the metal bromide used in preparing the ionic liquid-based metal organic framework is selected from indium bromide.

[0035] Experiments have shown that the metal-organic framework based on ionic liquid prepared using indium bromide as raw material has higher catalytic activity when catalyzing carbon dioxide cycloaddition reactions.

[0036] Preferably, the carbon dioxide cycloaddition reaction is carried out under normal pressure, the reaction temperature is 70 to 100° C., and the reaction time is 3 to 9 hours;

[0037] More preferably, the reaction temperature is 80 to 100°C.

[0038] Preferably, the epoxide is selected from one or more of epichlorohydrin, styrene oxide, benzyl glycidyl ether, and glycidyl phenyl ether;

[0039] More preferably, the epoxide is selected from one or more of epichlorohydrin, benzyl glycidyl ether, and glycidyl phenyl ether; more preferably, epichlorohydrin.

[0040] Compared with the prior art, the present invention has the following beneficial effects:

[0041] The invention discloses a method for preparing a metal organic framework based on ionic liquid. The preparation process is simple, the process conditions are mild and the time is short. Only short-time mixing at room temperature is required, and no high-temperature and high-pressure hydrothermal reaction is required to achieve chemical bonding between the ionic liquid and the metal, thereby preparing an ionic metal organic framework (MOFs) based on a biimidazole ionic liquid (IL) as an organic linker.

[0042] The ionic liquid-based metal organic framework prepared by the present invention is a catalyst with dual active centers (IL and metal ion), which is used to catalyze CO2 cycloaddition reaction, has high catalytic activity, and can achieve high conversion of substrates under normal pressure (CO2 pressure is 0.1MPa) and mild conditions (70-100°C, 3-9h). BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 This is the H NMR spectrum of the intermediate product ionic liquid [BPIM-IM]Ac prepared in Example 1;

[0044] Figure 2 The scanning electron microscope (SEM) and energy dispersive X-ray spectroscopy (EDS) mapping images of the product prepared in Example 1;

[0045] Figure 3 The Fourier transform infrared (FT-IR) spectrum of the product prepared in Example 1 is shown;

[0046] Figure 4This is the X-ray photoelectron spectroscopy (XPS) diagram of the product prepared in Example 1;

[0047] Figure 5 The scanning electron microscope (SEM) and energy dispersive X-ray spectroscopy (EDS) mapping images of the product prepared in Example 4;

[0048] Figure 6 This is the X-ray photoelectron spectroscopy (XPS) diagram of the product prepared in Example 4;

[0049] Figure 7 X-ray diffraction (XRD) patterns of the products prepared in Examples 1 to 6, respectively;

[0050] Figure 8 Thermogravimetric (TGA) curves of the products prepared in Examples 1 to 6, respectively;

[0051] Fig. 9 N2 adsorption-desorption isotherms of the products prepared in Examples 1 to 6, respectively;

[0052] Fig.10 It is a bar graph (a) of the ECH conversion rate in Application Examples 1 to 6, a bar graph (b) of the ECH conversion rate in Application Examples 7 to 21, a bar graph (c) of the ECH conversion rate in Application Examples 22 to 23, and a bar graph (d) of the conversion rate in Application Examples 24 to 26. DETAILED DESCRIPTION

[0053] In order to make the purpose, features and advantages of the present invention more obvious, the following further examples are listed to explain the present invention in detail. The following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the principles described in the present invention belong to the scope of protection of the present invention.

[0054] The endpoints and any values ​​of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in the present invention.

[0055] The terms used herein are only for describing specific embodiments and are not intended to limit the present disclosure. The terms "comprise", "include", etc. used herein indicate the existence of the features, steps, operations and / or components, but do not exclude the existence or addition of one or more other features, steps, operations or components.

[0056] All terms (including technical and scientific terms) used herein have the meanings commonly understood by those skilled in the art, unless otherwise defined. It should be noted that the terms used herein should be interpreted as having a meaning consistent with the context of this specification, and should not be interpreted in an idealized or overly rigid manner.

[0057] It should be noted that, unless otherwise defined, the technical terms or scientific terms used in the present invention shall have the usual meanings understood by persons with ordinary skills in the field to which the present invention belongs. If the full text involves descriptions such as "first", "second", etc., the descriptions such as "first", "second", etc. are only used to distinguish similar objects, and cannot be understood as indicating or implying their relative importance, order of precedence, or implicitly indicating the number of technical features indicated. It should be understood that the data described by "first", "second", etc. can be interchangeable under appropriate circumstances.

[0058] The raw materials used in the present invention are described as follows:

[0059] Indium bromide (InBr3, 99.9%), zinc bromide (ZnBr2, 99%), epichlorohydrin (ECH, ≥99.5%), styrene oxide (SO, 98%), benzyl glycidyl ether (BZGE, 99%), glyoxal solution (40%), and 1-(3-aminopropyl) imidazole (≥97%) were provided by Macklin (Shanghai, China). Formaldehyde solution (≥36%), glycidyl phenyl ether (GPE, >99.0%), and acetic acid (HAc, ≥99.5%) were provided by Aladdin (Shanghai, China). Unless otherwise specified, all other chemical reagents used were of analytical grade.

[0060] Example 1

[0061] (S1) Synthesis of 1,3-Bis(N-propylimidazolyl)imidazolium acetate ([BPIM-IM]Ac)

[0062] IL[BPIM-IM]Ac was prepared according to the following steps: 6.3 g of 1-(3-aminopropyl)imidazole (56 mmol), 9.1 g of acetic acid (HAc), 2.1 g of formaldehyde aqueous solution (36 wt%, 25 mmol), 3.6 g of glyoxal aqueous solution (40 wt%, 25 mmol) and 30 mL of water were stirred and mixed at room temperature (25°C, pH value of the system was 4.33) for 8 hours, and then 0.1 mol L -1 NaOH was used to adjust the pH to about 8. After removing water by distillation, the crude product was washed with ethyl acetate and acetone, respectively, and dried at 70°C to finally obtain a viscous brown liquid IL[BPIM-IM]Ac with a yield of 94%.

[0063]

[0064] By hydrogen nuclear magnetic resonance spectroscopy ( 1 H NMR, 400 MHz, DMSO-d6) confirmed its chemical structure. Figure 1 Chemical shift (δ, ppm): 1.619 (s, 3H), 2.279-2.348 (m, 4H), 2.510 (solvent residual signal), 3.574 (trace water signal), 4.036-4.070 (t, 4H), 4.163-4.198 (t, 4H), 6.886 (s, 2H), 7.210 (s, 2H), 7.661 (s, 2H), 7.789-7.793 (d, 2H), 9.684 (s, 1H).

[0065] (S2) Preparation of ionic liquid-based MOFs

[0066] 0.75 mmol of [BPIM-IM]Ac was weighed and dissolved in 10 mL of ethanol to obtain solution A, and 0.75 mmol of InBr3 was weighed and dissolved in 5 mL of ethanol to obtain solution B. After solution A and solution B were stirred and mixed at room temperature for 10 minutes, the resulting white powder was washed with ethanol and acetone, respectively. After vacuum drying for 8 hours (100°C), a white powder labeled InBr-[BPIM-IM]Ac-1 was obtained with a yield of 82%.

[0067] Figure 2 The scanning electron microscope (SEM) and energy dispersive X-ray spectroscopy (EDS) mapping diagram of the product prepared in this example show that the product is in a flake-like morphology; at the same time, the EDS mapping diagram shows that elements such as In, Br, C, N, and O are evenly distributed in MOFs.

[0068] Figure 3 This is the Fourier transform infrared (FT-IR) spectrum of the product prepared in this example, 3411cm -1 The absorption bands around 3119 cm are attributed to the stretching vibration of the OH group of water adsorbed on MOFs; -1 and 2950cm -1 The peaks at 1615 cm-1 are attributed to the CH stretching vibration of the imidazolium / imidazole ring and the stretching vibration of the CH2 group. -1 The peak at 1563 cm is attributed to the stretching vibration of C=O, while the peak at 1563 cm -1 、1525cm -1 and 1097cm -1 The three peaks at 1452 cm are related to the stretching vibration of the imidazolium / imidazole ring. -1 The absorption band is related to the asymmetric bending vibration of CH2.

[0069] Figure 4The X-ray photoelectron spectroscopy (XPS) diagram of the product prepared in this example shows that each C 1s XPS spectrum can be deconvoluted into three peaks, which are respectively attributed to CC (284.8 eV), CN / C=N (286.1 eV) and OC=O / C=NIL cation (288.3 eV). Each N 1s spectrum can be divided into three peaks, which are respectively located at 399.0 eV (C=N), 399.5 eV (CN) and 401.1 eV (NIL cation). In addition, compared with the lower metal / [BPIM-IM] + Compared with ionic MOFs, higher metal / [BPIM-IM] + The characteristic peaks of C=N in the ionic MOFs with a higher binding energy (399.0 eV (InBr-[BPIM-IM]Ac-1, InBr-[BPIM-IM]Ac-3) vs. 398.4 eV (InBr-[BPIM-IM]Ac-2)). This phenomenon may be attributed to the high metal / [BPIM-IM] + In the ionic MOFs with a high ratio, the N atom of the C=N bond undergoes significant electron transfer to the metal. In the O1s XPS spectrum, the characteristic peaks at 531.2eV–531.6eV are considered to be typical signals of acetate, while the characteristic peaks at 68.2eV–68.9eV correspond to the signals of Br 3d. The In 3d XPS spectrum shows two main peaks, located at 444.9eV–445.0eV (In 3d 5 / 2 ) and 452.5eV–452.7eV(In 3d 3 / 2 ).

[0070] Example 2

[0071] The preparation process is basically the same as that of Example 1, except that the molar number of InBr3 is replaced by 0.25 mmol in step (S2) (the initial molar ratio of InBr3 to [BPIM-IM]Ac is 1:3).

[0072] The product prepared in this example is recorded as InBr-[BPIM-IM]Ac-2, and the yield is 43%.

[0073] The SEM and EDS tests show that the product prepared in this example is Figure 2 similar.

[0074] Example 3

[0075] The preparation process is basically the same as that of Example 1, except that in step (S2), the molar number of InBr3 is replaced by 2.25 mmol (the initial molar ratio of InBr3 to [BPIM-IM]Ac is 3:1).

[0076] The product prepared in this example is recorded as InBr-[BPIM-IM]Ac-3, and the yield is 42%.

[0077] The SEM and EDS tests show that the product prepared in this example is Figure 2 similar.

[0078] Example 4

[0079] The preparation process is basically the same as that of Example 1, except that InBr3 is replaced by an equimolar amount of ZnBr3 in step (S2) (the initial molar ratio of ZnBr3 to [BPIM-IM]Ac is 1:1).

[0080] The product prepared in this example is recorded as ZnBr-[BPIM-IM]Ac-1, and the yield is 72%.

[0081] Figure 5 The scanning electron microscope (SEM) and energy dispersive X-ray spectroscopy (EDS) mapping images of the product prepared in this example show that the product has a flaky morphology. At the same time, the EDS mapping results show that elements such as Zn, Br, C, N, and O are uniformly distributed in MOFs.

[0082] Figure 6 The X-ray photoelectron spectroscopy (XPS) diagram of the product prepared in this example shows that each C 1s XPS spectrum can be deconvoluted into three peaks, which are respectively attributed to CC (284.8 eV), CN / C=N (286.0 eV) and OC=O / C=NIL cation (287.7 eV). Each N 1s spectrum can be divided into three peaks, which are respectively located at 399.0 eV (C=N), 399.3 eV (CN) and 401.0 eV (NIL cation). High Metal / [BPIM-IM] + The C=N peaks of the ionic MOFs appear at higher binding energies (399.0 eV–399.2 eV (ZnBr-[BPIM-IM]Ac-1, ZnBr-[BPIM-IM]Ac-3) compared to 398.0 eV (ZnBr-[BPIM-IM]Ac-2)), which may be due to the significant electron transfer from the N atom of the C=N bond to the metal. In the O 1sXPS spectrum, the peak at 531.2 eV is considered to be a typical signal of acetate, while the peak at 68.5 eV corresponds to the signal of Br3d. The Zn2p peaks are located at 1044.5 eV and 1021.5 eV, which can be attributed to Zn 2p, 1 / 2 and Zn 2p 3 / 2 .

[0083] Example 5

[0084] The preparation process is basically the same as that of Example 4, except that the molar number of ZnBr3 is replaced with 0.25 mmol in step (S2) (the initial molar ratio of ZnBr3 to [BPIM-IM]Ac is 1:3).

[0085] The product prepared in this example is recorded as ZnBr-[BPIM-IM]Ac-2, and the yield is 43%.

[0086] Example 6

[0087] The preparation process is basically the same as that of Example 4, except that the molar number of ZnBr3 is replaced with 2.25 mmol in step (S2) (the initial molar ratio of ZnBr3 to [BPIM-IM]Ac is 3:1).

[0088] The product prepared in this example is recorded as ZnBr-[BPIM-IM]Ac-3, and the yield is 53%.

[0089] Figure 7 The X-ray diffraction (XRD) patterns of the products prepared in Examples 1 to 6 respectively show that these MOFs have two diffraction peaks in the range of 12° to 12.6° and 22.7° to 24.5°, which is similar to the XRD pattern of zeolite imidazole framework (ZIFs). At the same time, the two diffraction peaks are relatively broad in shape, indicating that the ionic MOFs based on ILs are amorphous structures. This means that it is difficult to obtain detailed structural information. In order to further explore the structure of these MOFs, inductively coupled plasma spectroscopy (ICP-OES), ion chromatography (IC) and high performance liquid chromatography (HPLC) experiments were carried out. Experimental results show that the chemical compositions of these MOFs can be expressed as: In[BPIM-IM]Br3.5Ac0.5(InBr-[BPIM-IM]Ac-1), In[BPIM-IM]2Br3.1Ac1.9(InBr-[BPIM-IM]Ac-2), and In[BPIM-IM]Br3.8Ac0.2(InBr-[BPIM-IM]Ac-3).

[0090] Figure 8 Thermogravimetric (TGA) curves of the products prepared in Examples 1 to 6 respectively show that a significant mass loss occurs between 263°C and 500°C, and the onset decomposition temperature (Tonset) ranges from 263°C to 366°C, which is attributed to the decomposition of the imidazole / imidazolium rings in the ILs; the figure also shows that the Tonset value of Zn-based ion MOFs is higher than that of In-based ion MOFs.

[0091] The N2 adsorption-desorption isotherms (77K) of the products prepared in Examples 1 to 6 are measured, and the curves are shown in FIG. Fig. 9As shown, the results show that all ILs-based ionic MOFs exhibit type IV adsorption behavior, which indicates that each product has a mesoporous structure. Table 1 shows the specific surface area, pore size, pore volume and CO2 adsorption capacity data of each product obtained based on this test.

[0092] Table 1

[0093]

[0094] From the data in Table 1, we can find that the amorphous ILs-based ion MOFs have a smaller specific surface area (4.3 m 2 / g to 37.8m 2 / g), which is consistent with the characteristics of amorphous MOFs; and it was found that the CO2 adsorption capacity of Zn-based MOFs is higher than that of In-based MOFs.

[0095] Application Example 1 Cycloaddition reaction of CO2 and epichlorohydrin (ECH)

[0096] Using InBr-[BPIM-IM]Ac-1 prepared in Example 1 as a catalyst, 10 mmol of ECH and 50 mg (the mass ratio of catalyst to ECH is 5.4%) of catalyst were added to a 50 mL Schlenk reaction tube, which was sealed with a latex balloon filled with CO2 (CO2 pressure was 0.1 MPa), and flushed 3 times to replace the air in the tube. The reaction was then stirred at 80°C for 7 hours. After the cycloaddition reaction was completed, the solid catalyst and the liquid product were separated by centrifugation and the reaction was carried out using the reported method. 1 The yield of cyclic carbonates was determined by H NMR spectroscopy.

[0097] Application Examples 2 to 6

[0098] The preparation process is basically the same as that of Application Example 1, the only difference being that the catalysts are replaced with the products prepared in Examples 2 to 6 respectively, and the amount of each catalyst used is 50 mg.

[0099] The bar graphs of ECH conversion rates in Application Examples 1 to 6 are as follows: Fig.10 It was observed that In-based ion MOFs exhibited high catalytic performance, and InBr-[BPIM-IM]Ac-1 was selected as the best catalyst and used in subsequent experiments because it had the highest yield among all In-based ion MOFs.

[0100] The conversion rate data of ECH in Application Examples 1 to 6 are listed in Table 2 below.

[0101] Table 2

[0102]

[0103] Application Examples 7 to 21

[0104] The preparation process is basically the same as that of Application Example 1, the only difference being the adjustment of the temperature and time of the cycloaddition reaction.

[0105] The specific reaction conditions and ECH conversion rates in each application example are shown in the bar graph below. Fig.10 It was observed that the conversion of ECH increased with the increase of reaction temperature and time, and 80°C and 7 hours were considered to be the optimal reaction temperature and time, because under this condition, an ECH conversion of up to 98.1% could be obtained.

[0106] Application Examples 22-23

[0107] The preparation process is basically the same as that of Application Example 1, except that the mass of the catalyst is replaced with 30 mg (the mass ratio of the catalyst to ECH is 3.2%) and 60 mg (the mass ratio of the catalyst to ECH is 6.5%) respectively.

[0108] Comparative application example 1

[0109] The preparation process is basically the same as that of Application Example 1, except that no catalyst is added.

[0110] The bar graphs of ECH conversion rates in Application Examples 1, 22-23 and Comparative Application Example 1 are as follows: Fig.10 (c) is shown. It was observed that in the absence of a catalyst, the conversion of ECH was zero, while when the amount of catalyst was increased, the conversion of ECH increased because a larger amount of catalyst could provide sufficient active sites. Since 5.4% (mass ratio of catalyst to ECH) could provide an ECH conversion of up to 98.1%, it was selected as the optimal catalyst amount.

[0111] Application Examples 24-26

[0112] The preparation process is basically the same as that of Application Example 1, except that the types of epoxides are replaced with styrene oxide (SO), benzyl glycidyl ether (BZGE) and glycidyl phenyl ether (GPE) in sequence.

[0113] The bar graphs of conversion rates in various application examples are shown in Figure 2. Fig.10 (d) It was observed that the catalyst (InBr-[BPIM-IM]Ac-1) exhibited good catalytic activity for BZGE and GPE, with the yields of the corresponding cyclic carbonates ranging from 76.3% to 86.9%. The low conversion of SO may be related to the low reactivity of the β-carbon atom of SO due to the large steric hindrance of the benzene ring and the strong conjugation effect.

[0114] The conversion rate data in Application Examples 22 to 26 are listed in Table 3 below.

[0115] Table 3

[0116]

[0117] The above descriptions are only some specific embodiments of the present invention. It should be pointed out that a person skilled in the art can make many modifications and improvements. All modifications and improvements that do not exceed the scope of protection of the present invention should be regarded as within the scope of protection of the present invention.

Claims

1. A method for preparing a metal organic framework based on ionic liquid, characterized in that: The steps include: (S1) using short-chain imidazole and short-chain aldehyde as raw materials, and carrying out a quaternization reaction under acidic conditions to prepare a bisimidazole-type ionic liquid; (S2) mixing the bisimidazolium ionic liquid prepared in step (S1), the metal bromide and the solvent, and mixing them at room temperature for a period of time to obtain the ionic liquid-based metal organic framework.

2. The method for preparing a metal organic framework based on ionic liquid according to claim 1, characterized in that: In step (S1): The short-chain imidazole is selected from one or more of 1-(3-aminopropyl)imidazole, 1-(2-hydroxyethyl)imidazole, and 4,5-dimethylimidazole; The short-chain aldehydes are selected from one or more of formaldehyde, glyoxal, butyraldehyde, and glutaraldehyde; The molar ratio of short-chain imidazole to short-chain aldehyde is (1-2):

1.

3. The method for preparing a metal organic framework based on ionic liquid according to claim 1, characterized in that: In step (S1): The pH value of the acidic condition is 4.0 to 5.0; The quaternization reaction is carried out at room temperature.

4. The method for preparing a metal organic framework based on ionic liquid according to claim 1, characterized in that: In step (S2): The metal bromide is selected from indium bromide and / or zinc bromide; The solvent is selected from ethanol.

5. The method for preparing a metal organic framework based on ionic liquid according to claim 1, characterized in that: In step (S2): The molar ratio of the bisimidazolium ionic liquid to the metal bromide is 1:(0.3-3.0); The concentration of metal bromide in the solvent is 0.05-0.5 mol / L; Stir and mix at room temperature for not less than 10 min.

6. The method for preparing a metal organic framework based on ionic liquid according to any one of claims 1 to 5, characterized in that: The metal bromide is selected from indium bromide.

7. A metal organic framework based on ionic liquid prepared according to the method according to any one of claims 1 to 6.

8. A carbon dioxide cycloaddition reaction, using carbon dioxide and epoxide as raw materials, characterized in that: The metal organic framework based on ionic liquid described in claim 7 is used as a catalyst.

9. The carbon dioxide cycloaddition reaction according to claim 8, characterized in that: The carbon dioxide cycloaddition reaction is carried out under normal pressure, the reaction temperature is 70-100° C., and the reaction time is 3-9 hours.

10. The carbon dioxide cycloaddition reaction according to claim 8, characterized in that: The epoxide is selected from one or more of epichlorohydrin, styrene oxide, benzyl glycidyl ether, and glycidyl phenyl ether.